Upaya peningkatan keterampilan berbicara melalui media Kamishibai - Aufa, Novia Nurul; Triyono, Sulis (Journal of Culture, Literature and Foreign Language Teaching, 2025)
This reseacrh aims to find out (1) the improvement of German speaking skills and (2) the increase in the activeness of students at SMA Negeri 1 Minggir Sleman through the media of Kamishibai. This type of research is Classroom Action Research which is carried out in two cycles. Kemmis & Taggart (1992:6) stated that each action research cycle consists of four stages, planning, acting, observing, and reflection. The subjects of this study consisted of 36 students. The data in the study was obtained from observations, interviews, questionnaires, field notes, documentation, and assessment results. The data analysis technique used is qualitative descriptive. The results of this study show that there is an increase in German speaking skills and an increase in students' activeness in learning German at SMA Negeri 1 Minggir Sleman. There was an increase in the mean score of students' speaking skills by 13.7% and 100% of students stated that Kamishibai media helped in increasing the activity of learning German.